Synchronization of germinal vesicle maturity improves efficacy of in vitro embryo production in Holstein cows - Silva Soares, Ana Caroline [UNESP]; Gomes Marques, Kelly Nader; Martignoni Braganca, Luiz Gustavo; Lodde, Valentina; Luciano, Alberto Maria; Buratini, Jose [UNESP] (Elsevier B.V., 2020)
Germinal vesicle oocytes obtained by ovum pick-up (OPU) on a random day are heterogeneous in terms of chromatin maturity, and those with an intermediate degree of chromatin compaction present higher developmental competence. We previously developed a synchronization protocol combining follicle aspiration and FSH treatment capable of increasing the percentage of oocytes with intermediate chromatin compaction (classified as GV2 oocytes; within progressive stages of chromatin compaction ranging from GV0 to GV3) at the time of OPU. In this study, we tested the capacity of a similar protocol to synchronize oocyte chromatin maturity before OPU, as well as to improve the efficacy of in vitro embryo production (IVP) in Holstein cows. In the first experiment, eight non-lactating Holstein cows were subjected to the D5/4FSH, during which all follicles larger than 2 mm were aspirated and a progesterone intravaginal device was inserted on a random day (day 0). Subsequently, four IM injections of FSH (Folltropin; 40/40/20/20 mg) were administered 12h apart on days 2 and 3, and removal of the progesterone device and OPU were performed on day 5. Of the oocytes recovered by OPU, 83.2% were at the GV2 stage. In a second experiment, eighteen non- lactating Holstein cows (Synchro group) were subjected to the D5/4FSH protocol followed by IVM/IVF, and embryo production was compared with that of other seventeen cows submitted to OPU on a random day followed by IVM/IVF (Control group). Blastocyst rate in relation to total oocytes recovered was higher in the Synchro group (37.9%) compared to the Control group (21%; P < 0.05). The percentage of good quality blastocysts morphologically selected for freezing and later transfer in relation to the total number of oocytes recovered tended to be higher in the Synchro group (27.68%) compared to the Control group (14.34%; P = 0.1). These data suggest that synchronization protocols increasing the percentage of GV2 oocytes in the population subjected to IVM/IVF can improve the efficacy of embryo in vitro production in cattle. (c) 2020 Elsevier Inc. All rights reserved.
Keywords: OPU; Synchronization protocol; Germinal vesicle; Prematuration; Bos taurus; IVP